2000
DOI: 10.1210/endo.141.12.7823
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Newborn Male and Female Rats to Environmental Estrogens: Delayed and Sustained Hyperprolactinemia and Alterations in Estrogen Receptor Expression**This work was supported by NIH Grants ES-09555, ES-10154, and CA-80920; March of Dimes Grant 6-FY98–0159; and a grant from the Pardee Foundation. Preliminary results of this investigation were presented at the 82nd Annual Meeting of The Endocrine Society, Toronto, Canada, June 2000.

Abstract: Environmental estrogens (xenoestrogens) are synthetic compounds that are abundant in the environment and mimic natural estrogens. The estrogenicity of two such compounds, bisphenol A (BPA) and octylphenol (OP), during development of the neuroendocrine system was investigated. The objective was to compare the effects of neonatal exposure to BPA, OP, and diethylstilbestrol (DES), a potent synthetic estrogen, on prepubertal serum PRL levels and estrogen receptor (ER) expression in the anterior pituitary and media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(14 citation statements)
references
References 46 publications
(37 reference statements)
2
12
0
Order By: Relevance
“…Similarly, previous works have shown that ER expression in animals treated with other estrogenic compounds is significantly lower than that in control animals [20,35]. Interestingly, ER plays a role in mediating social recognition in female mice, as ERα and ERβ knockout mice have specifically impaired social recognition [6].…”
supporting
confidence: 55%
“…Similarly, previous works have shown that ER expression in animals treated with other estrogenic compounds is significantly lower than that in control animals [20,35]. Interestingly, ER plays a role in mediating social recognition in female mice, as ERα and ERβ knockout mice have specifically impaired social recognition [6].…”
supporting
confidence: 55%
“…A number of studies have been undertaken in order to check whether these chemicals alter the organizational effect of endogenous gonadal steroid hormones during the development of reproductive organs [1, 2, 3, 4, 5, 6, 7]. Most of these studies suggest that BBP and BPA exposure during differentiating and developmental stages exert irreversible effects on the reproductive organs as well as on the hypothalamic structures controlling reproductive functions.…”
Section: Introductionmentioning
confidence: 99%
“…In the ovary, both nuclear estrogen receptors [ 82 ] are known to be regulators of granulosa cell differentiation, follicle and oocyte growth, and ovulation. Several papers have already proposed roles for each of these receptors in ovarian physiology [ 83 , 84 , 85 ], with ERβ playing an important role in the follicle maturation process and ovulation [ 86 ].…”
Section: Discussionmentioning
confidence: 99%